Development of Aroma Extracts for use in the Brewing Industry using Novel Processing of Roasted Malt. - Foulkes, Andrew. R (2025)
Roasted malt is used in the brewing industry to impart beer with characteristic colour and aroma. Extraction of aroma compounds from hops using liquid and supercritical CO2 is practised commercially and allows more efficient use of hops as flavourings. Compared to traditional hop products, extracts are more consistent, with greater stability and are more concentrated in active materials for transportation and storage. The same benefits could be gained by producing an aroma extract of roasted malt. The research reported in this thesis thus investigated the feasibility of producing an aroma extract of roasted malt using CO2 extraction. In order to make this approach feasible, the concentration of aroma compounds in roasted malt was first maximised to facilitate a more efficient extraction. Attempts to increase the concentration of aroma compounds in roasted malt using novel roasting technology (TorWave™; Chapter 3) revealed that the aroma-forming reactions in malt broadly proceeded at similar rates under varying powers of Microwave heating if the same total rate of thermal input was applied by adjusting the fluidising air temperature. This means that the TorWave™ could be used to make products with equivalent concentrations of aroma compounds to traditional roasters. When the air temperature was varied to produce roasting profiles with different microwave powers but equivalent energy use, malt that was roasted using 4 kW of microwave power only had a significantly different (p<0.05) concentration of 4 out of 23 aroma compounds identified, compared to malt roasted using 0 kW of microwave power, TorWave™ processing could however alter the concentrations of aroma compounds formed in roasted products by changing the heat transfer intensity (rate of heat input, or intensity of roast). In Chapter 4 the impacts of changing crystal malt production process times and temperatures on flavour formation were discussed. Extending the duration of germination up to 6 days and stewing up to 24 h yielded an increase in aroma compounds of up to 6-fold compared to crystal malt that had been germinated and stewed for ‘standard’ times (4 days germination and 1 h stew at 65C). A new method of analysing the degree of starch gelatinisation was developed, using polarised light microscopy and image analysis. This revealed that not all starch granules were gelatinised, even after an 8 h stewing period. Increasing the amount of water available to facilitate starch degradation by mashing green malt before roasting/baking (Chapter 5) led to a statistically significant (p<0.05) increase in concentrations of aroma compounds in the final product, compared to stewed green malt. The new roasted malt product was termed ‘mashed malt’. Scaled up mashed malt that had been finished at three different baking temperatures (140, 180, and 220˚C) had a maximum increase of 20-fold compared to a standard lab crystal malt (4 days germination and 1 h stewing at 65˚C), which made it a suitable for extraction trials. The three types of scaled up mashed malt was extracted (Chapter 6) on a 5 mL CO2 extraction rig using ethanol as a co-solvent. GC-MS was used to identify three classes of compounds extracted from mashed malt: Maillard reaction products, ethanol adducts, and aliphatic compounds. Results showed that the extraction materials, which had significantly (p<0.05) smaller particle sizes, were extracted more efficiently. The effect of an extraction substrates particle size was confirmed by milling mashed malt using two methods (disc mill v hammer mill) and extracting it on a 500 mL extraction rig using an ethanol co-solvent. It was also shown that concentrations of maltol in the ethanolic extracts were as high as 10,045 ppm more than 773x more that its aroma threshold (13 ppm), by limiting the flow of ethanol co-solvent to prepare more concentrated extracts. At these concentrations the maltol component of the aroma extract would be detectable even on substantial dilution into finished beer. The research presented in this thesis has laid the groundwork to show that extracting aroma compounds from a highly flavoured roasted malt product using CO2 is feasible. The optimal conditions presented in this research were: using an extraction substrate with high concentrations of aroma compounds and small particle size, and minimising the volume of cosolvent by using a low percentage (2.5%) for a short time. More work is required to enhance processing such that a wider range of aromas could be extracted at sufficient concentrations.